Assessment of Genetic Diversity and Differentiation in Calamus flagellum, an Economically Important Rattan Species of North East Himalayas - Meena, Rajendra K.; Hansraj,; Sharma, Pratibha; Shanti,; Bhandari, Maneesh S.; Ginwal, Harish S. (Indian Forester, 2019)
India is endowed with vast biodiversity of rattan palms and key contributor to the livelihood of forest dwelling communities. The demand of the rattan resources is substantial but most of the raw material is being collected from natural stands, and therefore there is tremendous pressure on natural populations existed in reserve forests. The present study has been conducted to develop knowledge base on genetic diversity, differentiation and population structure of natural stands of Calamus flagellum in North East Himalayas using Inter Simple Sequence Repeat (ISSR) markers. A total of 204 bands were obtained in 51 individuals of C. flagellum when subjected to PCR amplification with 10 ISSR primers. Each primer was highly polymorphic producing 13 to 28 fragments across the genotypes. Relatively higher genetic diversity (I = 0.369) with a moderate level of genetic differentiation (GST = 0.248; PhiPT = 0.289) were recorded. Analysis of molecular variance revealed that large proportion of the genetic variation (71%) was confined among the individuals within populations. UPGMA dendrogram, Principal Coordinate Analysis and STRUCTURE analysis revealed that two ancestral groups captured the entire divisions of the sample. The data generated is of importance in devising programs for species conservation, management and improvement.